PENGARUH KOMPETENSI SUMBER DAYA MANUSIA,KOMITMEN ORGANISASI, DAN PEMANFAATAN TEKNOLOGI INFORMASI TERHADAP PENERAPAN AKUNTANSI AKRUAL PADA PUSKESMAS HIANG - Putra, Dori HP (Yudishtira Journal : Indonesian Journal of Finance and Strategy Inside, 2024)
Accrual-based government accounting standards have been implemented simultaneously in Indonesia since the enactment of Government Regulation Number 71 of 2010. However, in its implementation, not all regions are ready to immediately adopt it, one of the Hiang Health Centers. The unpreparedness of this implementation is caused by the lack of competence of human resources, organizational commitment and the use of information technology. This study aims to determine the influence of human resource competence, organizational commitment and the use of information technology on the level of application of accrual-based government accounting standards. The location of the research was carried out at the employees of the Hiang Health Center. The analysis tool used is multiple linear regression. The sample of this study is employees who are already Civil Servants, and non-civil servants. The results of this study show that the variables of human resource competence, organizational commitment and the use of information technology have a positive effect on the level of application of accrual-based government accounting standards at the Hiang Health Center